Analysis of multichannel optical rotary connectors based on the compensation operating principle with mirror and prismatic optical compensators (Part 1) - Shapar, V.M.; Lysenko, V.S.; Savchuk, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Performed in this work is a comprehensive theoretical computer analysis of performances inherent to two types of multichannel optical rotary connectors (ORC of compensation operation based on mirror and prismatic compensators. This analysis relies on exact analytical expressions obtained for light ray paths in ORC models with a mirror compensator made in the form of a bilateral mirror placed between two optical hemispheres and with a prismatic compensator made in the form of a Dove prism placed between two non-aberrational elliptic lenses. Found in ORC with the mirror compensator is the essential deficiency inherent to all these constructions, which is related to considerable rotary oscillations in the value of optical signals in mirror angular positions when the mirror halves the input light beam. In these mirror positions, the amplitude value of optical signal oscillations exceeds 95%, and optical losses are higher than –13 dB when the rotor turns. One deficiency more in these constructions is also strict technical requirements for the accuracy of making the optical components and mechanisms at the level of 1…2 µm. Concerning the ORC construction with a prismatic compensator as well as collimator and focusing lenses common for all the channels, one should note the inadmissibly high optical losses of the signal value (higher than –30…40 dB) in the case of construction with fiber-optic interfaces, and large dimensions and mass in the case of active construction with optoelectronic transducers at the inputs and outputs of ORC. For example, when the number of channels N = 10, the longitudinal dimension of the optical transfer channel (prism and lenses) exceeds 300 mm, and this dimension increases with increasing the number of channels. When this dimension is lower than 100 mm, the facility can be equipped with only one optical communication channel containing one LED and one photodiode located on the rotation axis. Optical losses in these constructions cannot be considered as satisfactory ones, since the respective loss value is higher than 18 dB for the number of channels N = 10.